Melaleuca alternifolia Essential Oil: Evaluation of Skin Permeation and Distribution from Topical Formulations with a Solvent-Free Analytical Method - Capetti, Francesca; Sgorbini, Barbara; Cagliero, Cecilia; Argenziano, Monica; Cavalli, Roberta; Milano, Luisella; Bicchi, Carlo; Rubiolo, Patrizia (Planta Medica, 2020)
Melaleuca alternifolia essential oil (tea tree oil) is widely used as an ingredient in skin care products because of its recognized biological activities. The European Scientific Committee on Consumer Products constantly promotes research and collection of data on both skin distribution and systemic exposure to tea tree oil components after the application of topical formulations. This study quantitatively evaluates permeation, skin layer distribution (stratum corneum, epidermis, and dermis), and release into the surrounding environment of bioactive tea tree oil markers (i.e., α-pinene, β-pinene, α-terpinene, 1,8-cineole, γ-terpinene, 4-terpineol, α-terpineol) when a 5% tea tree oil formulation is applied at a finite dosing regimen. Permeation kinetics were studied in vitro on pig ear skin using conventional static glass Franz diffusion cells and cells ad hoc modified to monitor the release of markers into the atmosphere. Formulation, receiving phases, and skin layers were analyzed using a fully automatic and solvent-free method based on headspace solid-phase microextraction/gas chromatography-mass spectrometry. This approach affords, for the first time, to quantify tea tree oil markers in the different skin layers while avoiding using solvents and overcoming the existing methods based on solvent extraction. The skin layers contained less than 1% of each tea tree oil marker in total. Only oxygenated terpenes significantly permeated across the skin, while hydrocarbons were only absorbed at trace level. Substantial amounts of markers were released into the atmosphere.
Keywords: Melaleuca alternifolia; Mirtaceae; tea tree oil; headspace solid phase microextraction; GC-MS; in vitro permeation kinetics; skin layer distribution